First Principles Modeling of Si/Ge Nanostructures for Photovoltaic and Optoelectronic Applications. Issue 10 (19th February 2018) - Marri, Ivan; Amato, Michele; Guerra, Roberto; Ossicini, Stefano
Abstract : We discuss results of ab initio calculations for Si, Ge, and Si/Ge nanowires and nanocrystals showing that theory can improve the comprehension of the properties of these systems. First, we consider doped and undoped freestanding hydrogenated nanowires and we explore their properties as a function of the size, geometry, and composition. Secondly, we focus the discussion on the electronic properties of matrix embedded Si, Ge, and Si/Ge nanocrystals by pointing out the role played by composition, quantum confinement, and strain. The discussed results show that, for Si/Ge nanowires, the interface between Si and Ge region plays an important role determining, in some case, the formation of a type II band offset, which is essential for photovoltaic applications. Moreover, for Si/Ge core–shell nanowires, it is shown that: i) selective doping results in the formation of hole or electron accumulation, with interesting consequences for the use of these materials in thermoelectrics and ii) through compensated doping, it is possible to tune the optical properties of these systems. For the embedded nanocrystals, the outcomes suggest that Ge nanocrystals can be suitable as optical absorption centers and that Si/Ge nanocrystals, owing to the localization of the band edge states, are interesting for photovoltaic cells. Abstract : In this work, Marri et al. discuss first‐principles calculations concerning the microscopic properties of Si, Ge, and Si/Ge nanowires (NWs) and nanocrystals (NCs). These systems are very interesting for their possible technological applications. The authors prove that electronic, optical, and transport properties of NWs can be tuned by changing composition and geometry. Moreover, the authors deeply analyze the role played by quantum confinement and by strain in Si, Ge, and Si/Ge NCs. The novelty and importance of these results may support further experimental investigation for the design of advanced Si‐ and Ge‐based nanodevices.